Case report: First report of haploidentical allogeneic hematopoietic stem cell transplantation from donors with mild alpha-thalassemia for acute leukemia - Zheng, Wenshuai; Wu, Yamei; Guan, Lixun; Cheng, Longcan; Hu, Yalei; Tan, Min; Yang, Yuhui; Ning, Hongmei (Frontiers in Oncology, 2022)
For acute leukemia (AL) with adverse prognostic factors, allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the standard care option after the first complete remission. Meanwhile, as the success of haploidentical HSCT (haplo-HSCT), haploidentical donors (HIDs) become a reliable choice. However, there have been no reports on haplo-HSCT from HIDs with mild alpha(α)-thalassemia for AL yet. In the present report, we first describe two cases of successful haplo-HSCT from HIDs with mild α-thalassemia for AL.